Effect of Proprioceptive Neuromuscular Facilitation on Basic Motor Skills in Children with Down Syndrome - Qurba Kiran Pt, Adnan Afzal, Hadia Anjum, Barira Shahid, Arooj Shahzad, Danish Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Trisomy 21 is a genetic disorder occurs in 92% individuals. Majority of the skeletal abnormalities are associated with it. Therefore the study had been planned with an aim to determine the effect of PNF on basic motor skills in child Down syndrome children. Methods: The study design was quasi-experimental. 22 children were included on inclusion &exclusion criteria. The data was collected from Rising Sun Institute for Special Children Lahore Group A was treated with conventional physical therapy whereas Group B were treated with PNF technique and conventional physical therapy. Pre-assessment was done by using GMFM. Each subject received 36 treatment sessions with 03 sessions per week. The session continued for 30 minutes for both groups. Post treatment reading for Gross Motor Function Measure was recorded after the end of 12 weeks. The collected data analyzed by using Statistical Package for Social Software (SPSS). Results: It showed that across the group comparison shows both treatments which are applied to both groups shows good results as their mean difference values show it and their P value are not significant. Results also showed that within the group comparison PNF has better results on group B patients as per their mean difference values show it and their p values are significant. Conclusion: The study concluded that the PNF technique has better effect in Down syndrome children as compared to conventional physical therapy treatment in children on gross motor skills like standing, walking, running jumping Keywords: Down syndrome (DS), Proprioceptive Neuromuscular Facilitation (PNF), Gross Motor Function Measure (GMFM).